Deciphering Guarapachangueo: Formulas and Formulaic Variation in Contemporary Rumba Percussion - Frías, Johnny (Current Musicology, 2023)
This article serves to further the conceptual and musical analysis of guarapachangueo, a key influence in the contemporary style of the percussion in Havana-style rumba. I follow Turino’s (2009) lead in distinguishing between improvisation and formulaic performance in analyzing the rhythmic vocabulary of guarapachangueo as a set of related formulas and variations. In doing so, I expand upon and refine some of the characteristics of guarapachangeuo described by Bodenheimer (2015), particularly the common and yet nebulous idea that the style entails increased improvisation in the lower register of the percussion. As an active performer of the style who specializes in the lower register percussion, I will draw upon my experiences and those of fellow rumberos, as well as commercial recordings and online videos of rumba in highlighting the structural formulas used in rumba’s contemporary rhythmic vocabulary. I argue that rather than increased improvisation, guarapachangueo comprises an aesthetic approach to playing rumba in which unique formulas are employed, representing a break with the standardized formulas of traditional rumba from the second half of the 20th century. These formulas produce a heightened sense of tension and release in which increased space and the interactive exchange of percussive phrases are central. Internalized by drummers, these formulas and variations become part of the performer’s musical habitus and are drawn upon—often unconsciously—by the musicians in the form of musical decisions that “say something” in the flow of a rumba performance.